Our own satellite link? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Despairing of the high costs and poor quality of phone services and access to the Internet, Paul Soddo of the Mbale Information Technology Center (PO Box 1655, Mbale, Uganda) complains of 'the lack of local exchange centres and Internet service...